Microcanonical Statistical Model for Fragmentation of Small Neutral Carbon Clusters - Nga, Do Thi (Communications in Physics, 2019)
We present the microcanonical statistical model to study fragmentation of small neutral carbon clusters Cn (n ≤ 9). This model describes, at a given energy, the phase space associated with all the degrees of freedom accessible to the system (partition of the mass, translation and ro- tation, spin and angular momentum of the fragments). The basic ingredients of the model (cluster geometries, dissociation energies, harmonic frequencies) are obtained, for both the parent cluster and the fragments, by an ab initio calculation. The fragmentation channels probabilities obtained as a function of the excitation energy, were compared with the experimental data at the Orsay Tandem. The deposited energy distributions were adjusted so that the experimental measure- ments were optimally reproduced. Two algorithms were used: Non-Negative Least Squares and Bayesien backtracing. The comparison of the theoretical and experimental probabilities shows a good global agreement. Both algorithms result in deposited energy distributions showing peaks. These peaks could be the signatures of specific molecular states which may play a role in the clus- ter fragmentation.